Synergetic Responses of Nonstructural Carbohydrates and Nutrients in Different Tree Organs to Drought - Wenqi He; Hongyan Liu; Wenqi Li; Jingyu Dai; Zidong Li; Yang Qi (Global Change Biology, 2026)
Non‐structural carbohydrates (NSCs) and nitrogen (N), phosphorus (P) facilitate the adaptation of trees to drought stress. There have been a large number of individual studies exploring NSCs and N, P changes in leaves, stems, and roots of different tree species during drought; however, an understanding of the general pattern across organs and interactions of NSCs and N, P responses to drought is still lacking. Here, we compiled 459 observations from 24 papers involving 32 tree species and conducted a meta‐analysis to evaluate the responses of non‐structural carbohydrates (NSCs) and nitrogen (N), phosphorus (P) concentrations in different tree organs (leaves, stems, and roots) to drought intensity. We found that the content of nitrogen and phosphorus decreases in leaves and roots while soluble sugars in leaves and starch in roots increases during drought. Roots prioritize nitrogen utilization during starch accumulation, whereas both nitrogen and NSCs accumulate in stems under drought, indicating distinct synergistic dynamics between roots and stems. During drought conditions, the shift in trees' starch‐to‐nitrogen (ST/N) ratio is negligible, indicating a coordinated response in the accumulation or allocation of starch and nitrogen. In contrast, the ratio of soluble sugars to nitrogen (SS/N) and soluble sugars to phosphorus (SS/P) increase, which indicates that they may function as indicators of short‐term storage or rapid response to drought. When compared to angiosperms, gymnosperms exhibit more pronounced changes in all tree non‐structural carbohydrates (NSCs)‐nutrient ratios (SS/N, SS/P, ST/N, ST/P). Our results highlight the interactions of NSCs and N, P responses to drought adaptation, which have been so far neglected and should be paid attention to in future studies.